1996
DOI: 10.1103/physrevb.54.6039
|View full text |Cite
|
Sign up to set email alerts
|

Importance of rings on the microscopic properties of a strong glass

Abstract: An optimized interparticle potential has been developed for its use in computer molecular dynamics simulations of vitreous boron trioxide ͑v-B 2 O 3 ) which includes four-particle interactions. This is required to force the formation of planar six-membered ͑boroxol͒ rings in such simulations. As a result, a better agreement with the static structure factor is achieved, even though the percentage of atoms taking part in such structures is relatively small. ͓S0163-1829͑96͒02934-7͔The presence of a substantial am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Wright and Sinclaire [5], Bray [6] and Zwanziger [7], found that 80% of boron atoms are included in the boroxol rings. Most molecular modeling studies [8,9] of B 2 O 3 came to different conclusions but generally the models could not reproduce the abundance of structural units building the borate network. Some improvements in the modeling of the borate network are the modifications introduced in the MD interactions by Cormack [10] leading to a relatively high fraction of 15-30% of boron in boroxol rings.…”
Section: Introductionmentioning
confidence: 96%
“…Wright and Sinclaire [5], Bray [6] and Zwanziger [7], found that 80% of boron atoms are included in the boroxol rings. Most molecular modeling studies [8,9] of B 2 O 3 came to different conclusions but generally the models could not reproduce the abundance of structural units building the borate network. Some improvements in the modeling of the borate network are the modifications introduced in the MD interactions by Cormack [10] leading to a relatively high fraction of 15-30% of boron in boroxol rings.…”
Section: Introductionmentioning
confidence: 96%
“…Although it is generally accepted that the molecular building block of vitreous B 2 O 3 is the planar BO 3 group, the manner in which the BO 3 triangles are connected has long been a matter of controversy. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The most widely accepted model for the structure of vitreous B 2 O 3 was for many years a random network of corner-linked triangles as suggested by Zachariasen. 9 Later, Krogh-Moe combined the results of many spectroscopic investigations and came to the conclusion that the BO 3 triangles prefer to form planar B 3 O 6 rings ͑see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] However, other interpretations of diffraction data have come to different conclusions. [19][20][21][22][23][24][25][26] The radial distribution functions for simple models containing a mixture of boroxol rings and BO 3 triangles with a variable fraction of boron atoms in boroxol rings were computed by Johnson et al 16 and later by Hannon et al 17 In the work of Johnson et al the results of the models were compared with the experimental real-space correlation function T(r) obtained from neutron diffraction in the range of 0-3 Å. The best agreement was obtained for a model containing 60% of the boron atoms in boroxol rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact a disordered network may be characterized in term of its ring distribution by shortest-path analysis [15]. Ring statistics has become the generally accepted measure of medium-range order in amorphous materials and it has been used to explain some physical properties of a-Si0 2 [16] as well as others common amorphous materials [17]. For Si0 2 a ring is defined as a closed path which is given by a sequence of O-Si-O atoms belonging the same tetrahedral unit (Si0 4 ).…”
Section: Resultsmentioning
confidence: 99%